Diagnostic Accuracy of Physical Examination for Detecting Arteriovenous Fistula Stenosis in Haemodialysis Patients - Rana Umar; Akram, Mateen; Naeem, Haris; Rehman, Faisal; Ali, Nauman; Aslam, Sehar; Ahmed, Waqar (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study was conducted to determine the accuracy of physical examination in detecting arteriovenous fistula stenosis in patients receiving maintenance hemodialysis. METHODOLOGY: A cross-sectional study was undertaken from October 2021 to March 2022, encompassing both outpatient and inpatient units of Nephrology and Cardiothoracic Surgery at Shaikh Zayed Hospital (SKZ), Lahore. This study evaluated 162 maintenance hemodialysis (MHD) patients selected through convenience sampling for the Presence of arteriovenous fistula (AVF) stenosis. The data were collected after the MHD session. After collecting demographics, patients underwent physical examinations performed by a trained nephrology resident, followed by colour Doppler sonography (CDS) performed by a radiologist blinded to the results of the physical examination (PE) for AVF stenosis. Cohen’s Kappa (?), positive predictive values (PPV), negative predictive values (NPV), sensitivity, and specificity were used to calculate the accuracy of PE for AVF stenosis. RESULTS: There was a strong agreement between PE and CDS regarding the diagnosis of AVF stenosis. The overall diagnostic accuracy of physical examination to detect AVF stenosis was 89.50% with PPV= 88.5%, NPV=90.7%, sensitivity= 91.7%, specificity=87.2%, and ?= 0.790. The diagnostic accuracy of physical examination to detect AVF inflow stenosis was 89.473% with PPV= 87.2%, NPV=90.7%, sensitivity= 82.9%, specificity=93.2%, and ?= 0.769. The diagnostic accuracy of physical examination to detect AVF outflow stenosis was 90.243% with PPV= 89.6%, NPV=90.7%, sensitivity= 86.0%, specificity=93.2%, and ?= 0.797. CONCLUSION: The findings of this study demonstrate that PE examination is a reliable method for regularly monitoring AVF patency.